EKSISTENSI KEHIDUPAN DI ALAM SEMESTA DALAM PERSPEKTIF TAFSIR AL-QUR’AN DAN SAINS - Mutmainah, Saroh; Nur Afifah; Adelia Ainun Nafis (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2026)
Advances in science and technology have opened up a new understanding that life may not only exist on Earth, but also has the potential to emerge elsewhere in the universe if the physical, chemical, and energy prerequisites are met. In the Islamic scientific tradition, the Qur’an has hinted at the basic elements of life long before modern science developed. This study aims to analyze the integration between scientific explanations regarding the prerequisites of life and the Qur’anic perspective on the origin and uniqueness of humans as caliphs on Earth. The research method uses literature studies with content analysis of tafsir sources and scientific literature. The results of the study show that there is consistency between the scientific concepts of water, soil, energy, and planetary habitability with Qur’anic verses. In addition, humans possess biological and spiritual specialness that distinguishes them from other creatures. This study emphasizes that the integration of science and revelation can strengthen human understanding of existence and their responsibilities in the universe.